ILLNESS PERCEPTION DAN SENSE OF COHERENCE (SOC) PADA PASIEN DIABETES MELITUS TIPE 2 - Christiani Natasya Miru; Krismi Diah Ambarwati (PSIKOVIDYA, 2020)
This study aims to determine whether or not there is a relationship between illness perception and Sense of Coherence (SOC) in patients with type 2 diabetes mellitus. Sense of Coherence (SOC) is a global orientation that states the extent to which a person has feelings of confidence that are persuasive, lasting, and dynamic that stimulus that comes from a person's internal and external environment in his life is something that is structured, predictable, and can be explained; resources available to someone to meet demands arising from the stimulus;claims are challenges and attachment to life, with one of the factors which affect SOC, namely illness perception. Participants in the study were 58 type 2 DM patients at the Kedungmundu Health Center, Semarang City. Data was collected using quantitative methods with a purposive sampling model. Based on the research results obtained correlation coefficient 〖(r〗_xy) = 0.536 with a significance value of 0.000 (p <0.05) which means there is a significant positive relationship between illness perception and Sense of Coherence in patients with type 2 Diabetes Mellitus in Kedungmundu Health Center Semarang City.